(R)‐Metacycloprodigiosin‐HCl: Chiroptical properties and structure. Issue 7 (10th May 2018) - Peixoto, Daniela; Ferreira, Elisabete P.; Lourenço, Ana M.; Johnson, Jordan L.; Lobo, Ana M.; Polavarapu, Prasad L.
Abstract: ( R )‐Metacycloprodigiosin can exist in three different tautomeric forms, each with hydrogens at C9′ and C12 in syn or anti orientation. With the addition of HCl, this structural diversity reduces to syn ‐( R )‐metacycloprodigiosin‐HCl (1a ) and anti ‐( R )‐metacycloprodigiosin‐HCl (1b ), each with multiple conformers. Energetics and chiroptical properties, namely, electronic circular dichroism (ECD) and specific optical rotation (SOR), of ( R )‐metacycloprodigiosin‐HCl have been investigated at B3LYP/6‐311++G(2d, 2p) level. The experimental ECD spectra of ( R )‐metacycloprodigiosin‐HCl have also been measured. Calculations indicated that the lowest energy conformer of1b is approximately 2.7 kcal/mol lower in energy than that of1a, and the energy barrier for anti to syn conversion is approximately 13 kcal/mol. The population weighted calculated SORs of1a and1b are, respectively, positive and negative. The respective calculated ECD spectra of these pseudoenantiomers show an almost mirror image relationship between them. The experimental SOR and ECD compare well with those predicted for1b . Thus, 1b is expected to be predominant, a situation confirmed also by nuclear Overhauser effect (NOE) data, with a similar conclusion reached for prodigiosin R1. Abstract :